The laboratory of proffesional practice, as an educational strategy, within the framework of curricular change - Bagdonavicius, María Julia (Revista del Hospital Italiano de Buenos Aires, 2019)
In view of the transformation that is taking place in university education in general and in education for health professionals in particular, it is that the University Institute of the Italian Hospital proposes a curricular change for the Medicine career. This implies a socio-cultural change that affects the different aspects of institutional life. It is proposed to leave behind the “Flexnerian system”, proposing a system based on: Problem Based Learning, in addition to workshops and laboratories where knowledge and skills will be acquired with a different degree of complexity in spiral form. The Professional Practice Laboratory is the space and educational environment where maximum integration occurs, working on all the necessary knowledge to carry out the corresponding professional activity. In the first module the focus was guided, fundamentally, to the communicational pursuing as objective: that the student develops skills that allow him to establish an adequate doctor-patient-family relationship, as well as adequate links, with the work team and the community. The evaluation was carried out to workshop itself and to the tutors through students’ quiz. The students were periodically evaluated by the tutors and at the end of the module with a written exam and a structured Objective Clinical Evaluation type test. For what we have worked to this moment, we believe that: The laboratory of professional practice, as a teaching strategy, contributes to the formation of complex skills; being the result of the evaluations and the feedback, fundamental to establish an improvement plan.